The Differences of Brain Based Learning and Somatic Auditory Visual and Intellectual Based on Brain Gym toward Students' Learning Outcomes and Retention - Aulia, Fitri Dayanti; Setiadi, Anandita Eka; Rahayu, Hanum Mukti (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to compare the Brain-Based Learning (BBL) and Somatic Auditory Visual and Intellectual (SAVI) learning models based on brain gym in an effort to improve student learning outcomes and retention. This study was experimental research with a Quasi-Experimental design. The population of this study totaling 62 people, using the BBL learning model for as many as 22 people and using the SAVI learning model for as many as 22 people. Data analysis used a t-test with SPSS for windows 22.0. The results showed that the average score of the pretest, posttest, and retest of the BBL class was greater than that of the SAVI class. The t-test analysis obtained a significance value of 0.026 <0.05 for learning outcomes and a significance value of 0.32 <0.05 for student retention. So it can be concluded that there is a significant difference between learning outcomes and retention in the BBL and SAVI learning models which affect learning outcomes and student retention in learning.